ANALYSIS FACTOR RISK GEOPOLITICS AND GLOBAL INFLATION AGAINST MOTIVATION OF INDONESIAN PEOPLE TO INVEST GOLD - Rakesh Sitepu; Anis Satu Rofiah; Arif Mustofa; Dwi Jeni Astutie; Erik Aprizal (PT. Radja Intercontinental Publishing, 2026)
This study examines the impact of geopolitical risk and global inflation on gold investment motivation am ong Indonesian investors, with perceived uncertainty acting as an intervening variable. Using a quantitative approach, data were collected from 250 respondents and analyzed through Structural Equation Modeling Partial Least Squares (SEM-PLS). The results indicate that geopolitical risk has a significant positive effect on perceived uncertainty, whereas global inflation does not exhibit a significant influence. Furthermore, neither geopolitical risk, global inflation, nor perceived uncertainty directly affect gold investment motivation. Mediation analysis confirms that perceived uncertainty does not significantly transmit the effects of macroeconomic pressures to gold investment motivation. These findings suggest that gold investment behavior in Indonesia is not solely driven by macroeconomic uncertainty but may depend on heterogeneous behavioral patterns. The study contributes to the behavioral finance literature by highlighting the limited direct role of global risk factors in shaping gold investment motivation and offers insights for policymakers and financial institutions in designing adaptive gold investment strategies.